Cannabis Use Is Associated With Increased Risk of Cigarette Smoking Initiation, Persistence, and Relapse Among Adults in the United States. Issue 8 (21st May 2019) - Weinberger, Andrea H; Delnevo, Cristine D; Wyka, Katarzyna; Gbedemah, Misato; Lee, Joun; Copeland, Jan; Goodwin, Renee D
Abstract: Introduction: Despite increasing use of cannabis, it is unclear how cannabis use is related to cigarette transitions. This study examined cannabis use and smoking initiation, persistence, and relapse over 1 year among a nationally representative sample of US adults. Methods: Data were from US adults (≥18 years) who completed two waves of longitudinal data from the Population Assessment of Tobacco and Health Study (Wave 1, 2013–2014; Wave 2, 2014–2015; n = 26 341). Logistic regression models were used to calculate the risk of Wave 2 incident smoking among Wave 1 never-smokers, smoking cessation among Wave 1 smokers, and smoking relapse among Wave 1 former smokers by Wave 1 cannabis use. Analyses were adjusted for age, gender, race/ethnicity, income, and education. Results: Among Wave 1 never-smokers, cannabis use was associated with increased odds of initiation of nondaily (adjusted odds ratio [AOR] = 5.50, 95% confidence limits [CL] = 4.02–7.55) and daily cigarette smoking (AOR = 6.70, 95% CL = 4.75–9.46) 1 year later. Among Wave 1 daily smokers, cannabis use was associated with reduced odds of smoking cessation (AOR = 0.36, 95% CL = 0.20–0.65). Among Wave 1 former smokers, cannabis use was associated with increased odds of relapse to daily and nondaily cigarette smoking (daily AOR = 1.90, 95% CL = 1.11–3.26; nondaily AOR = 2.33, 95% CL = 1.61–3.39). Conclusions: Cannabis use was associated with increased cigarette smoking initiation, decreased smoking cessation, and increased smoking relapse among adults in the United States. Increased public education about the relationship between cannabis use and cigarette smoking transitions may be needed as cannabis use becomes more common among US adults. Implications: As cannabis use increases in the United States and other countries, an evaluation of the relationships of cannabis use to other health-related behaviors (eg, cigarette smoking) is needed to understand the population-level impact of legalization. Little is known about associations between cannabis use and cigarette smoking transitions (1) using recent longitudinal data, (2) among adults, and (3) examining transitions other than smoking initiation (eg, smoking relapse). Our results suggest that among US adults, cannabis use was associated with increased cigarette smoking initiation among never-smokers, decreased cigarette smoking cessation among current smokers, and increased cigarette smoking relapse among former smokers.